Influência de diferentes fontes fotoativadoras na conversão de resinas compostas - Emerson Hamilton da Silva (2007)
This study evaluated the influence of different light sources on the conversion of different composite resins by Differential Scanning Calorimetry (DSC). Initially was determined the standard of the devices emission of light, one halogen light curing unit (Optilux 500 - Demetron/Kerr) and three generations of LEDs (LEC-470 I - MMOptics, Radii Plus - SDI and Ultra-Lume LED 5 - ULTRADENT), as for the spectrum and intensity. To measure the inorganic fraction of the composites (Durafill® VS - Heraeus-Kulzer, Tetric® Ceram - Ivoclar/Vivadent, Filtek Supreme XT - 3MESPE and Aelite LS Packable - Bisco) and its thermal stability, 3 specimens of each composite in cylindrical format, with 3mm of diameter and 1mm of depth, were confectioned, in a stainless steel matrix, light-cured and immediately submitted to the Thermogravimetry (TG). To the Differential Scanning Calorimetry (DSC), technique used in this experiment to determine the conversion of resin composites, 48 specimens were confectioned, in the same ratios of the used ones in the Thermogravimetry (TG). After to be removed of the matrix, each specimen was weighed in an analytical scale (SHIMADZU LIBROR AEG-SM - SHIMADZU CORP.), sealed in an aluminum crucible and taken for analysis. The data had been submitted to the analysis of variance test (p=0.002%) and Tukey test (p<0.05%). The results had allowed concluding that the intensity and compatibility of the spectral profile emitted by the light sources with the profile of absorption of the photoinitiators in composed resins have direct influence in the conversion during the polymerization process.